1981
DOI: 10.1002/bjs.1800680322
|View full text |Cite
|
Sign up to set email alerts
|

Arginine vasopressin release following surgical operations

Abstract: A study of plasma arginine vasopressin (AVP) concentrations in 16 patients undergoing uncomplicated cholecystectomy was carried out to determine the relative importance of the various stimuli to AVP secretion during and after an operation. Eight of the 16 patients were given a high epidural blockade from T4 and T12 and blood samples were taken before, at frequent intervals during and for two days after operation for determination of plasma AVP and osmolarity; systolic blood pressure was measured each time a bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 22 publications
0
11
0
4
Order By: Relevance
“…It is therefore common practice to recommend that intake should be restricted during and after surgery (5). Although ADH levels have been shown to be raised it is not clear whether this is in response to hypovolaemia and hypotension (6)(7)(8) or whether it is truly inappropriate in terms of both the osmolar and the volume status of the patient, as required by Bartter & Schwartz for the definition of the syndrome of inappropriate secretion of ADH (SIADH) (9). The distinction is important: if hypovolaemia is the cause of the raised ADH levels, fluid restriction will further reduce circulating volume and hence perfusion of vital organs.…”
mentioning
confidence: 99%
“…It is therefore common practice to recommend that intake should be restricted during and after surgery (5). Although ADH levels have been shown to be raised it is not clear whether this is in response to hypovolaemia and hypotension (6)(7)(8) or whether it is truly inappropriate in terms of both the osmolar and the volume status of the patient, as required by Bartter & Schwartz for the definition of the syndrome of inappropriate secretion of ADH (SIADH) (9). The distinction is important: if hypovolaemia is the cause of the raised ADH levels, fluid restriction will further reduce circulating volume and hence perfusion of vital organs.…”
mentioning
confidence: 99%
“…Earlier data (5Y8), together with the observation that AVP levels rapidly normalized until postoperative day 2 or 3, point to an important role of the neuroendocrine stress response in the perioperative and postoperative secretion of AVP. Accordingly, two studies have shown that the peak intraoperative AVP response occurs shortly after skin incision (5,6).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, vasopressin inhibits intestinal motility (Mitchell and Collin 1985). It is released as a part of stress response following surgical trauma and after the use of opiates (Cochrane, et al 1981); (Weiskopf, et al 1987). The exact mechanism by which vasopressin mediates dysmotility is not clear.…”
Section: Pathophysiologymentioning
confidence: 99%